Low-temperature S-doping on N-doped TiO2 films and remarkable enhancement on visible-light performance. (December 2019) - Yan, Jiancheng; Zhao, Juan; Hao, Liang; Hu, Yifei; Liu, Tongyang; Guan, Sujun; Zhao, Qian; Zhu, Zheng; Lu, Yun
Graphical abstract: Highlights: Low-temperature S-doping on N-doped TiO2 films was achieved at 80 °C. S-doping led to the decrease in band gap from 3.01 to 2.81 eV. Water is easier to chemically dissociate to form OH − species owing to S-doping. S doping made the photocatalytic activity of N-doped TiO2 increased by 4.0 times. Abstract: Sulfur doping of nitrogen-doped TiO2 nanograss array films was realized through facile thiourea solution immersion at a low temperature of 353 K. Doped nitrogen and sulfur atoms were found mainly in the interstitial form. Nitrogen doping (N-doping) and sulfur doping (S-doping) enhanced visible light absorption and decreased the band gap of undoped TiO2 films from 3.10 to 3.01 and 2.81 eV, respectively. Furthermore, N-doped and N, S co-doping made the water absorbed on TiO2 was easier to chemically dissociate and generate hydroxide groups. N-doping favored to produce more O 2 − radicals and S-doping benefit to generate more O H radicals. Both O H and O 2 − active radicals played a significant role in the degradation of RhB. The photocatalytic activity of undoped TiO2 films was increased by 2.5 times by N-doping through urea treatment. By further S-doping, the photocatalytic performance of N-doped TiO2 films was enhanced by 4.0 times again.